Dopaminergic Neurotransmission in Patients With Parkinson's Disease and Impulse Control Disorders: A Systematic Review and Meta-Analysis of PET and SPECT Studies - Martini, Alice; Dal Lago, Denise; Edelstyn, Nicola M. J.; Salgarello, Matteo; Lugoboni, Fabio; Tamburin, Stefano (Frontiers in Neurology, 2018)
Background Around 30% Parkinson’s disease (PD) patients develop impulse control disorders (ICDs) to D2/3 dopamine agonists and, to a lesser extent, levodopa. We aim to investigate striatal dopaminergic function in PD patients with and without ICD. Methods PubMed, Science Direct, EBSCO, and ISI Web of Science databases were searched (from inception to March 7, 2018) to identify PET or SPECT studies reporting striatal dopaminergic function in PD patients with ICD (ICD+) compared to those without ICD (ICD-). Studies which included drug naïve patients, explored non-pharmacological procedures (e.g., deep brain stimulation), and those using brain blood perfusion or non-dopaminergic markers were excluded. Standardized mean difference (SDM) was used and random-effect models were applied. Separate meta-analyses were performed for dopamine transporter level, dopamine release, and dopamine receptors availability in the putamen, caudate, dorsal and ventral striatum. Results A total of 238 studies were title and abstract screened, of which 19 full-texts were assessed. Nine studies (ICD+: N=117; ICD-: N=175 patients) were included in the analysis. ICD+ showed a significant reduction of dopamine transporter binding in the putamen (SDM=-0.46; 95% CI: -0.80, -0.11; Z= 2.61; p=0.009), caudate (SDM=-0.38; 95% CI: -0.73, -0.04; Z= 2.18; p=0.03) and dorsal striatum (SDM=-0.45; 95% CI: -0.77, -0.13; Z= 2.76; p=0.006), and increased dopamine release to reward-related stimuli/gambling tasks in the ventral striatum (SDM=-1.04; 95% CI: -1.73, -0.35; Z= 2.95; p=0.003). Dopamine receptors availability did not differ between groups. Heterogeneity was low for dopamine transporter in the dorsal striatum (I2=0%), putamen (I2=0%) and caudate (I2=0%), and pre-synaptic dopamine release in the dorsal (I2=0%) and ventral striatum (I2=0%); heterogeneity was high for dopamine transporter levels in the ventral striatum (I2=80%), and for dopamine receptors availability in the ventral (I2=89%) and dorsal (I2=86%) striatum, putamen (I2=93%), and caudate (I2=71%). Conclusions ICD+ patients show lower dopaminergic transporter levels in the dorsal striatum and increased dopamine release in the ventral striatum when engaged in reward-related stimuli/gambling tasks. This dopaminergic imbalance might represent a biological substrate for ICD in PD. Adequately powered longitudinal studies with drug naïve patients are needed to understand whether these changes may represent biomarkers of premorbid vulnerability to ICD.